The Culture of Patient Safety in Anesthesiology Nursing Services - Ni Luh Putu Lusiana Devi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patient safety principles have not been optimally implemented in anesthesiology services. Nurse anesthetists, as providers of anesthetic nursing services, must have a good patient safety culture so that they can ensure patients remain safe during the anesthesia process. This study aims to determine the description of patient safety culture among nurse anesthetists in Indonesia. This quantitative study with a cross-sectional approach involved 369 nurse anesthetists as samples. The sampling technique used was purposive sampling. The research instrument used was the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire developed by the Agency for Healthcare Research and Quality (AHRQ) in Indonesian, with a Cronbach's Alpha value of ≥ 0.70 and a range of 0.809-0.918 for all items consisting of 12 components. Data analysis in this study used descriptive statistics, namely frequency distribution with percentage or proportion measures. This study shows that the majority of nurse anesthetists have a patient safety culture in the poor category (57%), with the lowest scores in the dimensions of non-punitive response to errors and staffing, while the highest scores were in the dimension of teamwork within the unit. Service providers need to take proactive measures to identify and change system weaknesses at all levels of service.